Primary adenosquamous carcinoma of the esophagus: an analysis of 39 cases - Ni, Peng-Zhi; Yang, Yu-Shang; Hu, Wei-Peng; Wang, Wen-Ping; Yuan, Yong; Chen, Long-Qi (Journal of Thoracic Disease, 2016)
Background: Adenosquamous carcinoma (ASC) of the esophagus is an uncommon type of malignant esophageal neoplasm containing both squamous cell carcinoma (SCC) and adenocacinoma (AC) components. The aim of this study was to explore the clinical characteristics and prognosis of esophageal ASC. Methods: A retrospective review of esophageal ASC patients who underwent transthoracic esophagectomy with lymphadenectomy in our hospital from July 2007 to April 2014. Results: A total of 39 (1.0%) esophageal ASC patients among 3855 patients with esophageal cancers were collected to analyze. There were 34 men and 5 women with a median age of 61.0 years (range from 39–85). Median follow-up time was 30.0 months and median survival time was 44.4 months. The 1-, 3- and 5-year overall survival rates were 82.1%, 51.6% and 37.5%, respectively. Compared to esophageal SCC and AC, there were no significant difference in survive time (P=0.616). Thirty five (92.1%) of the 38 patients who underwent preoperative endoscopic biopsy were misdiagnosed, mostly as SCC. Fifteen patients (38.5%) were found to have lymph node metastasis. Thirty two patients (82.1%) had a poorly differentiated or undifferentiated tumor. According to the 2009 American Joint Committee on Cancer (AJCC) staging system for esophageal squamous cell carcinoma, 3 patients were at Stage I, 21 patients at Stage II and 15 patients at Stage III. In univariate analysis, pT stage, lymph node metastasis and pTNM Stage significantly influenced survive time. In multivariate analysis, however, only lymph node metastasis (P=0.003; 95% CI: 1.626–10.972) was found to be the independent prognostic factor. Conclusions: Primary ASC of the esophagus is a rare disease with difficultly to be histologically confirmed by endoscopic biopsy. The prognosis of esophageal ASC was no worse than esophageal SCC and AC. Lymph node metastasis is the most influent prognostic factor. The TNM staging system of esophageal SCC is applicable for esophageal ASC.